2020
DOI: 10.18632/oncotarget.27758
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the metabolic dependencies of the broad amino acid transporter SLC6A14

Abstract: Tumor cells typically enhance their metabolic capacity to sustain their higher rate of growth and proliferation. One way to elevate the nutrient intake into cancer cells is to increase the expression of genes encoding amino acid transporters, which may represent targetable vulnerabilities. Here, we study the regulation and function of the broad amino acid transporter SLC6A14 in combination with metabolic stress, providing insights into an uncharacterized aspect of the transporter activity. We analyze the patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…SLC6A14 SLC6A14, also known as amino acid transporter B 0,+ (ATB 0,+ ), maintains a unidirectional influx of glutamine, coupled with 2 Na + and 1 Cl -, along a transmembrane gradient 98 . Given the functional role of SLC6A14 in extending the range of amino acid uptake (including glutamine and leucine, both of which are activators of mTORC1), as well as providing substrates for SLC1A5 and SLC7A5, the molecule has attracted much attention 99,100 . Indeed, SLC6A14 is overexpressed in colon, cervical, ER-positive breast, and pancreatic cancer cells and is associated with their proliferation [101][102][103][104] .…”
Section: Slc38a1 and Slc38a2mentioning
confidence: 99%
“…SLC6A14 SLC6A14, also known as amino acid transporter B 0,+ (ATB 0,+ ), maintains a unidirectional influx of glutamine, coupled with 2 Na + and 1 Cl -, along a transmembrane gradient 98 . Given the functional role of SLC6A14 in extending the range of amino acid uptake (including glutamine and leucine, both of which are activators of mTORC1), as well as providing substrates for SLC1A5 and SLC7A5, the molecule has attracted much attention 99,100 . Indeed, SLC6A14 is overexpressed in colon, cervical, ER-positive breast, and pancreatic cancer cells and is associated with their proliferation [101][102][103][104] .…”
Section: Slc38a1 and Slc38a2mentioning
confidence: 99%
“…SLC6A14 (also known as ATB0 + ) is reported as a plasma membrane Na + /Cl − -dependent transporter (co-transport of two Na + , one Cl − and one amino acid molecule) of a range of amino acids, upregulated in cancer 42 46 for which serine is a theoretical substrate 20 , 47 . Functional characterization of human SLC6A14 in Xenopus oocytes using electrophysiology and radiolabeled amino acid uptake experiments, suggested that SLC6A14 can transport 18 of the 20 proteinogenic amino acids (with aspartate and glutamate the exceptions).…”
Section: Resultsmentioning
confidence: 99%
“…We found that transcriptional signatures of DATPs showed marked increases in the genes regulating metabolic process, especially in the amino acid synthesis (Fig EV2A and B ). Importantly, DATPs showed much higher expression of solute carrier transporters such as Slc7a5 / Lat1 and Slc3a2 , which form a heterodimeric complex and uptake essential amino acid (EAA) from the extracellular region (Yanagida et al , 2001 ; Dejure et al , 2020 ) (Fig 3A ). Previous studies revealed that subsets of EAA transporters, such as Slc7a5 / Lat1 , are directly regulated by YAP/TAZ (Hansen et al , 2015 ; Park et al , 2016 ).…”
Section: Resultsmentioning
confidence: 99%